Beneficial effects of statin treatment after myocardial infarction: Is progenitor cell mobilization the missing link? - Tousoulis, D; Kaski, J; Antoniades, C; Stefanadis, C (2008)
It is widely accepted that statin treatment improves survival in patients with myocardial infarction. Evidence also suggests that aggressive statin treatment is superior than standard dose during the post-infarction period. However, the exact mechanisms are still not well understood. Endothelial progenitor cells (EPC) play a key role in vascular homeostasis, since they contribute to the repair of damaged endothelium post-myocardial infarction, while they induce neoangiogenesis. Recent evidence suggests that statins may exert their beneficial effect in patients with recent myocardial infarction, by inducing EPC mobilization, and this may be a key mechanism by which statins improve survival in these patients. However, large scale clinical trials remain to prove that aggressive statin treatment is superior than standard dose in these patients, by inducing a more effective EPC mobilization.